Molten carbonate fuel cell system fed with biofuels for electricity production. (2nd November 2016) - Chiodo, V.; Zafarana, G.; Maisano, S.; Freni, S.; Galvagno, A.; Urbani, F.
Abstract: This study investigates on the efficiency of integrated reformer-MCFC system. Performances of a Ni catalyst working under steam reforming conditions of three different bio-fuels (biogas, ethanol and glycerol) are experimentally evaluated. Reformers outlet stream were applied as fuel for a MCFC stack in order to estimate the total integrated system efficiencies. It is found that the large amount of heat (20%–54% of the inlet fuel – LHV basis) is employed for the reforming of the biofuel during the heating phase of inlet stream to the reforming operative temperature. Moreover, among the examined biofuels the highest amount of externally supplied energy (∼79% of the inlet fuel – LHV basis) is wasted in the fuel processor unit for the steam reforming of ethanol, mostly due to the high amount of the water required (S/C = 4.2 mol/mol). Finally, it is also found that the combined biogas reformer-MCFC system is exhibited the highest electrical efficiency (76%). Highlights: Different biofuels reformers combined with a MCFC system were analyzed. The electric power released by MCFC was fixed at 125 kWe. Mass balance for each bio-fuels reformer was calculated. The efficiencies of the reformer-stack MCFC integrated system for power generation were evaluated.